CONTROL AND OPTIMIZATION OF VOLTAGE PROFILES AND SAG MITIGATION IN LOW-VOLTAGE POWER NETWORKS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Voltage sags, swells, and fluctuations in low-voltage networks can disrupt sensitive equipment, reduce industrial productivity, and accelerate component aging. This paper reviews common assessment practices, including ITIC/CBEMA curves and waveform analysis, and proposes an enhanced method that also considers pre- and post-event intervals to better quantify disturbance severity and recovery behavior. A disturbance direction detection procedure is presented to support source localization and targeted mitigation. As an alternative to conventional UPS-based solutions, active voltage conditioners (AVC)/dynamic voltage restorers (DVR) are discussed for fast compensation without energy storage and with high tolerance to voltage variations, while not covering complete interruptions. The main contribution is a combined DVR/AVC and active filtering solution that improves voltage stability, power factor, and harmonic content, enabling a cleaner, more reliable supply.
Keywords: Voltage regulation; Voltage sag; Active voltage conditioner; Dynamic voltage restorer; Harmonic filters